Centrality of positive and negative autobiographical memories across adult life span. Issue 3 (26th April 2022) - Pociunaite, Justina; Zimprich, Daniel; Wolf, Tabea
Abstract: Previous studies have found that in nonclinical samples centrality of positive events is usually higher than centrality of negative events. In this study, we investigated the centrality and its relation to valence by considering additional predictor variables (i.e., intensity, time since event, self‐concept clarity) as well as age group differences. A total of 365 participants aged between 18 and 89 reported up to 10 positive and up to 10 negative autobiographical memories. We used multilevel analysis to account for the hierarchical structure of the data. The results confirmed the higher centrality of positive events, but only for middle‐aged and older adults. Intensity contributed to the centrality of both positive and negative events, whereas self‐concept clarity was relevant regarding negative memories of young and middle‐aged adults only. Hence, the extent to which memories contribute to identity is not only depending on characteristics of memories but on the remembering person as well.